Coercion and public justification. (August 2014) - Bird, Colin
According to recently influential conceptions of public reasoning, citizens have the right to demand of each other 'public justifications' for controversial political action. On this view, only arguments that all reasonable citizens can affirm from within their diverse ethical standpoints can count as legitimate justifications for political action. Both proponents and critics often assume that the case for this expectation derives from the special justificatory burden created by the systematically coercive character of political action. This paper challenges that assumption. While conceding that citizens who propose to deploy the coercive apparatus of the state to enforce controversial legislation owe their fellows a justification that overcomes the strong presumption against coercing agents, it denies that this consideration can explain why public justifications are also required. Having argued that the public justification requirement is not among the justification conditions for public coercion, the paper then proposes an alternative rationale for the expectation that political action be publicly justified. On this alternative, the case for the public justification requirement depends on democratic citizens' standing as legislative co-authors, and not on considerations having to do with their liability as private individuals to coercion at the hands of the state.